The effect of wildfire on scattered trees, 'keystone structures', in agricultural landscapes. (15th September 2016) - Crane, Mason; Lindenmayer, David B.; Cunningham, Ross B.; Stein, John A. R.
Abstract: Scattered trees are considered 'keystone structures' in many agricultural landscapes worldwide because of the disproportionate effect they have on ecosystem function and biodiversity. Populations of these trees are in decline in many regions. Understanding the processes driving these declines is crucial for better management. Here, we examine the impact of wildfire on populations of this keystone resource. We examined 62 observation plots affected by wildfire and matched with 62 control observation plots where fire was absent. Counts of scattered trees were conducted pre‐fire in 2005 and repeated post‐fire in 2011. Changes in populations were compared between the control and fire‐affected observation plots. Our results show wildfire had a significant local impact, with an average decline of 19.9% in scattered tree populations on burned plots. In contrast, scattered trees increased on average by 5.3% in the control observation plots. The impact of wildfire was amplified (as revealed by greater percentage tree losses) by larger wildfires. Wildfire effects on scattered tree populations are of concern, given a background of other (usually) chronic stressors (often associated with agriculture) and that the frequency and intensity of wildfire are predicted to increase in many landscapes.